Strategi transformasi digital untuk meningkatkan daya saing perbankan syariah di era industri 4.0 - Ni'maturofi'ah, Dewi (Maliki Interdisciplinary Journal, 2025)
This study analyzes the implementation of strategic management and digital transformation within the Islamic banking industry in Indonesia. In the digital era, Islamic banks face both opportunities and challenges in adopting technologies such as artificial intelligence, blockchain, and the Internet of Things (IoT). Digital transformation is essential to enhance competitiveness, operational efficiency, and financial inclusion within Islamic banking, as customers increasingly prefer faster and more secure banking services. However, this transformation encounters obstacles due to low levels of Islamic financial literacy, as well as limitations in technological infrastructure and human resources. Proposed solutions include improving Islamic financial literacy, investing in digital infrastructure, and collaborating with fintech companies to expand service reach. The findings of this study suggest that a well-executed digital transformation strategy can not only enhance competitiveness but also foster innovation in products and services, making them more inclusive and aligned with Sharia principles.